To amend, repeal or enact: Analysing the legislation that regulate anti-illicit financial flows in Namibia's Natural Resources Sector - Zongwe, Leezola R (Department of Private Law, 2022)
This dissertation is premised on the understanding that the legislation meant to curtail illicit financial flows (IFFs) in Namibia is poorly drafted and does not adequately curtail IFFs in the country's natural resource sector resulting in low levels of domestic resource mobilization. IFFs refer to the illegal gain and/or movement of money between entities and persons. Namibia's natural resources span from its sustainable fishing sector to various non renewable mineral resources such as uranium, gold, diamonds, tin, copper, cadmium, lead, lithium, vanadium, salt, and zinc. The country is resource rich and politically stable. However, despite this its industrialization is stagnant and its development is rudimentary with about a third of its population living in extremely poor socio-economic conditions. Over the past decade, it has become increasingly evident that Namibia's efforts to curb IFFs have not yielded the desired results. In this regard, Namibia's anti-illicit financial flow laws do not adequately prevent IFFs within the natural resources sector. To paint the full picture of Namibia's anti-IFF legal framework, this dissertation engages in the monism versus dualism debate to ascertain Namibia's position concerning international law within its territory. Evaluating Namibia's international law position and the treaties that apply in Namibia allows this dissertation to ascertain whether the country can use international law to better equip its law enforcement, regulators, and courts with more effective rules for regulation and prosecution. Following this evaluation, this dissertation analyses Namibia's national laws aimed at curbing IFFs in its natural resource sector. From this analysis, this dissertation draws its conclusion that, although there are a few gaps within these laws, the identified shortcomings are material in that their absence greatly undermines the aims and functions of the legislation and their enforcement bodies. Finally, this dissertation proffers recommendations to cure the mischief identified.